Electrocatalysts: Nitrogen‐Doped Nanoporous Carbon/Graphene Nano‐Sandwiches: Synthesis and Application for Efficient Oxygen Reduction (Adv. Funct. Mater. 36/2015). (September 2015) - Wei, Jing; Hu, Yaoxin; Liang, Yan; Kong, Biao; Zhang, Jin; Song, Jingchao; Bao, Qiaoliang; Simon, George P.; Jiang, San Ping; Wang, Huanting
Abstract : On page 5768, Huanting Wang and co‐workers report the synthesis of zeolitic‐imidazolate‐framework (ZIF)/graphene oxide (GO) sandwich‐like composites with ultrasmall ZIF nanocrystals (≈20 nm in size) that fully cover the GO via a homogenous nucleation followed by uniform deposition and confined growth process. The ZIF/GO composites are further converted to N‐doped nanoporous carbon/graphene nano‐sandwiches, which act as non‐precious metal catalysts with excellent performance for electrochemical oxygen reduction reaction.